2008
DOI: 10.1183/09031936.00140507
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of treatment changes in 6-minute walk distance in patients with COPD

Abstract: There is uncertainty about the interpretation of changes in the 6-min walk distance (6MWD) in chronic obstructive pulmonary disease (COPD) patients and whether the minimal important difference (MID) for this useful outcome measure exists.Data were used from nine trials enrolling a wide spectrum of COPD patients with 6MWD at baseline and follow-up and used to determine threshold values for important changes in 6MWD using three distribution-based methods. Anchor-based methods to determine a MID were also evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
196
8
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(234 citation statements)
references
References 53 publications
17
196
8
9
Order By: Relevance
“…In this context, some authors have suggested that correlation coefficients of the relationship should be o0.5 for interpreting anchor-based approaches results satisfactorily. In the case of correlation coefficients between 0.3 and 0.5, the analyses can be performed but the interpretation of the results and estimates requires some caution [26,28]. With correlation coefficients amounting to 0.48 and 0.45 for endurance time and endurance distance, respectively, and considering the present estimates are very similar to what was previously reported, we are confident about the validity of the proposed estimates.…”
Section: Determination Of Mid Values For Eswtsupporting
confidence: 78%
See 1 more Smart Citation
“…In this context, some authors have suggested that correlation coefficients of the relationship should be o0.5 for interpreting anchor-based approaches results satisfactorily. In the case of correlation coefficients between 0.3 and 0.5, the analyses can be performed but the interpretation of the results and estimates requires some caution [26,28]. With correlation coefficients amounting to 0.48 and 0.45 for endurance time and endurance distance, respectively, and considering the present estimates are very similar to what was previously reported, we are confident about the validity of the proposed estimates.…”
Section: Determination Of Mid Values For Eswtsupporting
confidence: 78%
“…As previously suggested [13,25,26], different methods should be combined for the determination of MID values, considering that there is no consensus in favour of a single best methodology for the determination of MID estimate and that this estimate should be viewed as a range of probable values rather than as a discrete value.…”
Section: Determination Of Mid Values For Eswtmentioning
confidence: 99%
“…According to the values proposed by different investigators (19,20), 31 patients (32%) presented clinically significant worsening (≥54 m) and in 36 patients (38%) the decrease in 6MWD was ≥35 m. The proportion of patients with a minimum clinically significant decline ranged from 50 to 58% among patients with severe or very severe disease. The Charlson index increased significantly during the study period [3 (3-4) vs 4 (3-5); P = 0.009].…”
Section: Resultsmentioning
confidence: 99%
“…The distance covered is reported in meters. There are two different references to define the minimum clinically significant decline in 6MWD (19,20): a reduction ≥54 m (19) or ≥35 m (20) from baseline. In this study, we evaluated the 6MWD decline according to both definitions.…”
Section: Exercise Tolerancementioning
confidence: 99%
“…In COPD patients a distance of 54 m has been identified for the MCID, although more recently this value has been questioned and the threshold for MCID may be lower in this group (PUHAN et al [26] suggest 35 m) [27]. Based on a large cohort of 822 IPF patients the MCID for the 6MWD was calculated to be 24-45 m, depending on the statistical method employed [28].…”
Section: Figurementioning
confidence: 99%